(untitled) (Global Journal of Medical Research, 2023)
Background Leprosy is one of the neglected and poverty-related diseases in low and middle-income countries the disease is associated with socioeconomic factors poor knowledge of the victims to report cases and poor access to health facilities with a definitive diagnosis of the associated lesions In most cases patients are reluctant to report the infection earlier because of the insidious nature of the infection Thus the study was conducted to determine the prevalence of leprosy in eastern Tanzania Material and methods A retrospective study design was undertaken by analysing the patient s biodata at Nazareth leprosy centre located in Ifakara Tanzania The analysis was to determine the association of the disease with age sex location type of lesions presented disease detection technique and the time for reporting to the centre The Chi-square and t-test were used to determine the association of the factors with disease causation at the p-value of 0 05